1992
DOI: 10.1577/1548-8659(1992)121<0067:lhasod>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Status of Delta Smelt in the Sacramento-San Joaquin Estuary, California

Abstract: The delta smelt Hypomesus transpaciftcus is endemic to the upper Sacramento-San Joaquin estuary. It is closely associated with the freshwater-saltwater mixing zone except when it spawns in fresh water, primarily during March, April, and May. The delta smelt feeds on zooplankton, principally copepods. Its dominant prey was the native copepod Eurytemora affinis in 1972-1974 but the exotic copepod Pseudodiaptomus forbesi in 1988. Because the delta smelt has a 1 -year life cycle and low fecundity (mean, 1,907 eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
201
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(205 citation statements)
references
References 17 publications
3
201
1
Order By: Relevance
“…As most fish grow, they progress to larger foods, such as mysids, amphipods and other epibenthic invertebrates. Filter feeders such as American (Alosa sapidissima) and threadfin (Dorosoma petenense) shad, and planktivores such as delta and longfin (Spirinchus thaleichthys), smelt remain largely tied to the pelagic food web, although they use epibenthic organisms such as mysids at least periodically (Moyle et al 1992;Feyrer et al 2003;Feyrer et al 2007;Slater and Baxter 2014).…”
Section: Diagram 5-secondary Production To Predatorsmentioning
confidence: 99%
“…As most fish grow, they progress to larger foods, such as mysids, amphipods and other epibenthic invertebrates. Filter feeders such as American (Alosa sapidissima) and threadfin (Dorosoma petenense) shad, and planktivores such as delta and longfin (Spirinchus thaleichthys), smelt remain largely tied to the pelagic food web, although they use epibenthic organisms such as mysids at least periodically (Moyle et al 1992;Feyrer et al 2003;Feyrer et al 2007;Slater and Baxter 2014).…”
Section: Diagram 5-secondary Production To Predatorsmentioning
confidence: 99%
“…To gain a better understanding of the extent of this ecological interaction between Delta Smelt and Mississippi Silversides, knowledge of the life history of both species is crucial. However, though multiple studies have described the biology and population dynamics of Delta Smelt (Moyle et al 1992;Bennett 2005;Feyrer et al 2007;Merz et al 2011;Sommer et al 2011;Sommer and Mejia 2013;Rose et al 2013), little is known about the life history and habitat associations of Mississippi Silversides within the Delta. Characterizing the abundance and distribution of this invasive species with environmental factors may provide insight into what has allowed Mississippi Silverside to become so widespread and abundant in this system.…”
Section: Introductionmentioning
confidence: 99%
“…In the San Francisco Estuary, previous studies indicated that some zooplankton and young (larval and juvenile) fishes maintain peak abundance in or near the LSZ Moyle et al 1992;Kimmerer et al 1998). Furthermore, the degree of retention in this low-salinity and nursery habitat is considered a potentially important mechanism regulating recruitment success and population dynamics.…”
mentioning
confidence: 99%
“…In this paper, we investigate the degree of flexibility in behavioral responses by native and exotic species to changing hydrodynamics to shed light on mechanisms that may contribute to the nursery habitat potential of the LSZ in the San Francisco Estuary Moyle et al 1992;Jassby et al 1995;Bennett and Moyle 1996). This work was part of an interdisciplinary investigation to evaluate the potential relationships between the hydrodynamics of the LSZ and the abundance and vertical distribution of zooplankton and young fishes under a range of freshwater river-flow conditions.…”
mentioning
confidence: 99%